Foreign bank ownership and income inequality: empirical evidence. Issue 11 (2nd March 2020) - Delis, Manthos D.; Hasan, Iftekhar; Mylonidis, Nikolaos
ABSTRACT: Using country-level panel data over 1995–2013 on within-country income inequality and foreign bank presence, this paper establishes a positive relation between the two, running from higher foreign bank presence to income inequality. Given that foreign bank participation increased by 62% over the period 1995 to 2013, our baseline results imply a 5.8% increase in the Gini coefficient on average over this period, ceteris paribus . These results are robust to the inclusion of country and year fixed effects and to the use of restrictions on foreign bank entry in the host countries as an instrumental variable. We show that this positive effect is channelled through the lack of greenfield entry and the associated lower levels of competition.